Nauka a konkurencyjność małej firmy - Golińska-Pieszyńska, Małgorzata (Science and Competitiveness of Small Firms, 2007)
In economic practice in Poland, science and industry sectors function separately from each other. In this situation the great role has local government. This article presents the competitiveness of small firms as one of many elements of the Regional Innovation Strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 49-58